4-Phenylbutyrate Benefits Traumatic Hemorrhagic Shock in Rats by Attenuating Oxidative Stress, Not by Attenuating Endoplasmic Reticulum Stress. Issue 7 (July 2016) - Yang, Guangming; Peng, Xiaoyong; Hu, Yi; Lan, Dan; Wu, Yue; Li, Tao; Liu, Liangming
Abstract : Objective: Vascular dysfunction such as vascular hyporeactivity following severe trauma and shock is a major cause of death in injured patients. Oxidative stress and endoplasmic reticulum stress play an important role in vascular dysfunction. The objective of the present study was to determine whether or not 4-phenylbutyrate can improve vascular dysfunction and elicit antishock effects by inhibiting oxidative and endoplasmic reticulum stress. Design: Prospective, randomized, controlled laboratory experiment. Setting: State key laboratory of trauma, burns, and combined injury. Subjects: Five hundred and fifty-two Sprague-Dawley rats. Interventions: Rats were anesthetized, and a model of traumatic hemorrhagic shock was established by left femur fracture and hemorrhage. The effects of 4-phenylbutyrate (5, 20, 50, 100, 200, and 300 mg/kg) on vascular reactivity, animal survival, hemodynamics, and vital organ function in traumatic hemorrhagic shock rats and cultured vascular smooth muscle cells, and the relationship to oxidative stress and endoplasmic reticulum stress was observed. Measurements and Main Results: Lower doses of 4-phenylbutyrate significantly improved the vascular function, stabilized the hemodynamics, and increased the tissue blood flow and vital organ function in traumatic hemorrhagic shock rats, and markedly improved the survival outcomes. Among all dosages observed in the present study, 20 mg/kg of 4-phenylbutyrate had the best effect. Further results indicated that 4-phenylbutyrate significantly inhibited the oxidative stress, decreased shock-induced oxidative stress index such as the production of reactive oxygen species, increased the antioxidant enzyme levels such as superoxide dismutase, catalase, and glutathione, and improved the mitochondrial function by inhibiting the opening of the mitochondrial permeability transition pore in rat artery and vascular smooth muscle cells. In contrast, 4-phenylbutyrate did not affect the changes of endoplasmic reticulum stress markers following traumatic hemorrhagic shock. Furthermore, 4-phenylbutyrate increased the nuclear levels of nuclear factor-E2–related factor 2, and decreased the nuclear levels of nuclear factor κB in hypoxic vascular smooth muscle cells. Conclusions: 4-phenylbutyrate has beneficial effects for traumatic hemorrhagic shock including improving animal survival and protecting organ function. These beneficial effects of 4-phenylbutyrate in traumatic hemorrhagic shock result from its vascular function protection via attenuation of the oxidative stress and mitochondrial permeability transition pore opening. Nuclear factor-E2–related factor 2 and nuclear factor-κB may be involved in 4-phenylbutyrate-mediated inhibition of oxidative stress. Abstract : Supplemental Digital Content is available in the text.